Surveying with construction applications - Kavanagh, Barry F.; Slattery, Dianne Kay (Pearson Education Limited, 2015)
Known for its state-of-the-art coverage and clear, concise approach, Surveying with Construction Applications, Eighth Edition covers the latest advances and foundational principles of surveying. Covering both principles and a wide range of contemporary applications, it is well-suited to Fundamentals courses, Applications courses, or both. Revisions focus on recent improvements in instrumentation technology, field data capture, and data processing, describing how these change the way surveyors interact with construction professionals and engineers. The authors emphasize sound measurement technique and accurate documentation throughout. To overcome the limited math skills brought by many new students, they have added an easy-to-read math review chapter, preparing students for all relevant construction layout computations.